SHORT TERM TREATMENT OF CHRONIC HYPERKALEMIA WITH ORAL POTASSIUM BINDER IN CHRONIC KIDNEY DISEASE PATIENTS - Sulejman, Sabir; Karanfilovik, Angela; Stojanoska, Ana; Milenkova, Mimoza; Usprcov, Julijana; Kolonja, Bleron; Salkoski, Izet; Minovska, Hristina; Memeti, Adrian; Spasovska, Adrijana; Ristevski, Oliver (Journal of Morphological Sciences, 2024)
The aim of our study was to analyse the efficacy of short-term administration of oral calcium polystyrene sulfonate (CPS) to treat hyperkalemia in non-dialysis CKD patients. A prospective interventional study was conducted in 65 CKD patients with chronic hyperkalemia with a month of therapy. Patients were stratified into groups in respect of potassium level (mild <5.9; moderate 6-6.5; severe â‰¥6.5 mmol/l). Regression analysis was applied to investigate associations of hyperkalemia with different variables. Paired T-Test was used for comparative analysis of potassium levels before and after therapy.   Patients mean age was 67 years, eGFR ranged between 8 to 52ml/min. More than half of patients presented with moderate or severe hyperkalemia.None of the demographic, clinical or pharmacological variables predicted potassium level. The comparative analysis with paired samples T-Test showed significantly lower potassium levels after one month of therapy (p<0.001). The portion of patients that were encountered for mild hyperkalemia significantly increased (21% vs. 59%, p<0.001) and conversely, the portions of those with moderate and severe hyperkalemia significantly decreased (29% vs. 3%, p<0.001; 15% vs, 3%, p<0.001), respectively. Short term treatment of hyperkalemia with oral potassium binder is effective in non-dialysis CKD patients. Key words: hyperkalemia, potassium binder, CKD, GFR, RAAS therapy.